Alien Abduction Experience: Definition, neurobiological profiles, clinical contexts and therapeutic approaches - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2020)
Starting from the general concept of "alien abduction experience", the present work focuses on the essential aspects of the disorder defining the clinical and diagnostic contexts, laying the foundations for correct differential diagnosis, without neglecting the neural characteristics elaborated in the scientific community. The discussion concludes with the best therapeutic approaches suggested on the subject, paying particular attention to analyzing the related profiles and those related to the presumed discovery of alien implants in the human body of patients.